CONCEPTUAL THREE PHASE ITERATIVE MODEL OF KDD (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
KDD process includes how data is stored and accessed, how andwhat algorithms can apply to large amount of data efficiently,how results can be interpreted and visualized. KDD is theprocess of identifying valid, interesting and understandablepatterns in data. In this paper we will describe conceptual threePhase Iterative Model of KDD. The main layers of this purposedmodel are: Philosophy Layer, Technique Layer and ApplicationLayer. We will also perform the comparison of Tradition KDDModel with Three Phase Iterative Model.